Guest Editors: Educational And Management Researches In The Islamic World - Ayad N. Abdullah; Kirembwe Rashid Abdul Hamed; Zainal Abidin Hajib; Mohd Rosmizi Abd Rahman (Universiti Sains Islam Malaysia, 2024)
Given the importance of educational field worldwide, the educational process has been and continues to be a major focus of interest for researchers. The process of teaching and learning is therefore subjected to constant updating with the aim of making adjustments for the better outcomes. Thus, among aims of educational research is to discuss educational process in order to develop teaching professions. Such types of research have direct implications for the modernization of teaching and learning patterns as well as development of learning activity, outcomes and the quality and of education. Bearing these contexts in minds, we selected a number of informative educational research in Arabic language conducted in Arabian Gulf region including the Sultanate of Oman and Saudi Arabia that analyzed various aspects. Thus, we have suggested to publish them in a special issue of the Al-Abqari Journal for God's sake.